Development of learning-based chemistry devices guided discovery to improve critical thinking skills - I Nyoman Loka; Wildan Wildan; Jeckson Siahaan; Mukhtar Haris; Lalu Rudyat Telly Savalas (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
Learning tools have been developed through lesson plans, worksheets based on learning-guided discovery, and assessment instruments to improve critical thinking skills on the sub-subject factors that affect the reaction rate. The stages carried out in the production process of the two types of learning devices are defining, planning, and development, which are the three stages of the four stages of the 4D model. Two lecturers and one teacher validate the quality of the developed learning tools. Based on the results of data analysis, the lesson plan as a whole has good quality, the student worksheet is in the very good category, and the instrument for assessing students' chemical critical thinking skills has a high category of validity. Based on the integration of learning model guided discovery, the lesson plan and student worksheet have very good quality, and the integration of critical thinking skills in the assessment instrument is very good.